CONDITIONS OF EDUCATION OF VISUALLY IMPAIRED CHILDREN IN INCLUSIVE EDUCATIONAL ENVIRONMENT - Khusnuddinova Zulaiho Khamidullayevna; Nuriddinova Madina Oktam kizi (Web of Journals Publishing, 2023)
This article discusses the conditions of involving visually impaired children in inclusive education and teaching in an inclusive educational environment.
Keywords: Inclusive education, types of children with disabilities, education of visually impaired children, referral of visually impaired children to inclusive education and conditions imposed on them.